2020
DOI: 10.1530/rep-20-0015
|View full text |Cite
|
Sign up to set email alerts
|

New insights in equine steroidogenesis: an in-depth look at steroid signaling in the placenta

Abstract: Steroid production varies widely among species, with these differences becoming more pronounced during pregnancy. As a result, each species has its own distinct pattern of steroids, steroidogenic enzymes, receptors, and transporters to support its individual physiological requirements. Although the circulating steroid profile is well characterized during equine pregnancy, there is much yet to be explored regarding the factors that support steroidogenesis and steroid signaling. To obtain a holistic view of ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 86 publications
5
15
0
Order By: Relevance
“…Enzymes present later in the steroidogenic pathway, including HSD17B1, HSD17B2, HSD3B2 and CYP19A1 are present across gestation, albeit at relatively lower levels in the 45-day allantochorion than later gestational ages (Loux et al 2020). These data are consistent with the work from the groups of both Raeside and Sharp which found that equine embryos produce estrogens in extraembryonic membranes as well as in the ICM (Raeside et al 2012) as early as 12 days of gestation (Zavy et al 1984).…”
Section: Chorioallantois (Allantochorion)supporting
confidence: 88%
See 1 more Smart Citation
“…Enzymes present later in the steroidogenic pathway, including HSD17B1, HSD17B2, HSD3B2 and CYP19A1 are present across gestation, albeit at relatively lower levels in the 45-day allantochorion than later gestational ages (Loux et al 2020). These data are consistent with the work from the groups of both Raeside and Sharp which found that equine embryos produce estrogens in extraembryonic membranes as well as in the ICM (Raeside et al 2012) as early as 12 days of gestation (Zavy et al 1984).…”
Section: Chorioallantois (Allantochorion)supporting
confidence: 88%
“…Steroidogenesis-related transcripts tell a similar story of a transitioning tissue, as well as providing hints into tissue physiology. For example, the 45-day allantochorion produces high levels of the enzymes required for cholesterol synthesis as well as STAR, CYP11A1 and CYP17A1, suggesting that, as in the rabbit, this early tissue is able to effectively synthesize cholesterol de novo, as well as mediate conversion to the Δ5 androgen DHEA (Loux et al 2020). A strong correlation exists between these placental enzyme transcripts and DHEAS in maternal circulation (r > 0.978; P < 0.001; Legacki et al 2019), lending credence to a placental origin for DHEAS.…”
Section: Chorioallantois (Allantochorion)mentioning
confidence: 99%
“…The chemical transformations in the left column represent the delta5-pathway and those in the right column the delta4-pathway. Genes indicated are encoding enzymes involved in the processes those so far identified by transcriptome analysis during the pregnancy of mares ( Loux et al, 2020 ). CYP, cytochrome P450; GST, glutathione transferase; HSD, hydroxysteroid dehydrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation of the equine transcriptome in chorioallantois and endometrium at several time points throughout gestation has established GST A3-3 among the actors in endocrinology ( Loux et al, 2020 ). Figure 7 shows enzymes identified in the horse via their transcripts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation